Brine waste from seawater desalination in Malaysia: assessment on public awareness and understanding - Mahadi, Cynthia; Kasmuri, Norhafezah; Miskon, Mohd Fuad (IOP Publishing Ltd, 2024)
Water scarcity is a growing concern, and saltwater desalination is being explored as a potential solution, including in Malaysia. Therefore, it is important to assess public awareness of the outcome of desalination and the harmful effects of improper disposal of brine in the ecosystem. Hence, a survey was conducted and analyzed using the relative importance index method to gather information on public awareness of brine waste management practices and the negative impacts of brine waste. One hundred respondents from the public in Malaysia were randomly selected for this sample study. The results indicated that the public has an average level of awareness about desalination. Despite that, their perception of brine waste and its impact on the ecosystem ranges from average to high. Nevertheless, the study also reveals significant findings related to the low understanding among Malaysians regarding the detrimental effects of untreated brine wastewater disposal. Thus, the experts emphasize the importance of education and awareness to the public and encourage the government to implement stricter regulations on brine disposal with more effective policies. Moreover, the output of this paper gauged the public awareness level in Malaysia regarding the increasing use of desalination technology and the potential negative consequences of brine waste. It later equips the policymakers with the necessary information to make well-informed decisions by actively engaging the understanding of local communities' needs, perspectives, and aspirations on matters that directly affect them.